HELLP Syndrome or Acute Fatty Liver of Pregnancy: A Differential Diagnostic Challenge - Rath, Werner; Tsikouras, Panagiotis; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2020)
HELLP syndrome and the less common acute fatty liver of pregnancy (AFL) are unpredictable, life-threatening complications of pregnancy. The similarities in their clinical and laboratory presentations are often challenging for the obstetrician when making a differential diagnosis. Both diseases are characterised by microvesicular steatosis of varying degrees of severity. A specific risk profile does not exist for either of the entities. Genetic defects in mitochondrial fatty acid oxidation and multiple pregnancy are considered to be common predisposing factors. The diagnosis of AFL is based on a combination of clinical symptoms and laboratory findings. The Swansea criteria have been proposed as a diagnostic tool for orientation. HELLP syndrome is a laboratory diagnosis based on the triad of haemolysis, elevated aminotransferase levels and a platelet count < 100 G/l. Generalised malaise, nausea, vomiting and abdominal pain are common symptoms of both diseases, making early diagnosis difficult. Clinical differences include a lack of polydipsia/polyuria in HELLP syndrome, while jaundice is more common and more pronounced in AFL, there is a lower incidence of hypertension and proteinuria, and patients with AFL may develop encephalopathy with rapid progression to acute liver failure. In contrast, neurological symptoms such as severe headache and visual disturbances are more prominent in patients with HELLP syndrome. In terms of laboratory findings, AFL can be differentiated from HELLP syndrome by the presence of leucocytosis, hypoglycaemia, more pronounced hyperbilirubinemia, an initial lack of haemolysis and thrombocytopenia < 100 G/l, as well as lower antithrombin levels < 65% and prolonged prothrombin times. While HELLP syndrome has a fluctuating clinical course with rapid exacerbation within hours or transient remissions, AFL rapidly progresses to acute liver failure if the infant is not delivered immediately. The only causal treatment for both diseases is immediate delivery. Expectant management between 24 + 0 and 33 + 6 weeks of gestation is recommended for HELLP syndrome, but only in cases where the mother can be stabilised and there is no evidence of foetal compromise. The maternal mortality rate for HELLP syndrome in developed countries is approximately 1%, while the rate for AFL is 1.8 – 18%. Perinatal mortality rates are 7 – 20% and 15 – 20%, respectively. While data on the long-term impact of AFL on the health of mother and child is still insufficient, HELLP syndrome is associated with an increased risk of developing cardiovascular, metabolic and neurological diseases in later life.HELLP-Syndrom und die seltenere akute Schwangerschaftsfettleber (AFL) sind unvorhersehbare, lebensbedrohliche Komplikationen in der Schwangerschaft. Klinische und laborchemische Gemeinsamkeiten stellen den Geburtshelfer häufig vor eine differenzialdiagnostische Herausforderung. Bei beiden Erkrankungen besteht eine mikrovesikuläre Steatose unterschiedlicher Ausprägung. Ein spezifisches Risikoprofil ist für beide Entitäten bisher nicht bekannt. Als gemeinsame prädisponierende Faktoren gelten genetische Defekte in der mitochondrialen Fettsäureoxidation sowie Mehrlingsschwangerschaften. Die Diagnose AFL wird aus der Kombination klinischer Symptome und laborchemischer Befunde gestellt, die Swansea-Kriterien stellen dabei eine diagnostische Orientierung dar. Das HELLP-Syndrom ist eine laborchemische Diagnose aus der Trias Hämolyse, erhöhte Transaminasen und Thrombozytopenie < 100 G/l. Allgemeines Krankheitsgefühl, Übelkeit, Erbrechen und Abdominalschmerzen sind gemeinsame Symptome beider Erkrankungen, die eine frühe Diagnosestellung erschweren. Klinische Unterschiede bestehen in der beim HELLP-Syndrom fehlenden Polydipsie/Polyurie und dem bei AFL häufigeren und ausgeprägteren Ikterus, dem selteneren Auftreten von Hypertonie und Proteinurie sowie in der Entwicklung einer Enzephalopathie bei zunehmendem Leberversagen. Beim HELLP-Syndrom stehen neurologische Symptome wie starke Kopfschmerzen und Visusstörungen im Vordergrund. Laborchemisch ist die AFL durch die Leukozytose, die Hypoglykämie, die ausgeprägtere Hyperbilirubinämie, die initial fehlende Hämolyse und Thrombozytopenie < 100 G/l, die Verminderung der Antithrombin-Spiegel < 65% und die Verlängerung der Prothrombinzeit vom HELLP-Syndrom abzugrenzen. Während das HELLP-Syndrom in Schüben mit passageren Remissionen verlaufen kann, geht die AFL, sofern keine rasche Entbindung erfolgt, in ein akutes Leberversagen über. Die einzige kausale Therapie beider Erkrankungen ist die unverzügliche Entbindung. Beim HELLP-Syndrom wird zwischen der 24 + 0 – 33 + 6 SSW ein exspektatives Vorgehen empfohlen, sofern die Mutter stabilisierbar ist und keine fetale Gefährdung besteht. Die mütterliche Letalität beträgt beim HELLP-Syndrom in den Industrieländern ca. 1%, bei der AFL 1,8 – 18%, die perinatale Mortalität 7 – 20% bzw. 15 – 20%. Während bei der AFL die Langzeitauswirkungen auf Mutter und Kind bisher nicht geklärt sind, muss beim HELLP-Syndrom mit einem erhöhten Risiko für kardiovaskuläre, metabolische und neurologische Erkrankungen im späteren Leben gerechnet werden.
Keywords: HELLP syndrome; acute fatty liver of pregnancy; Swansea criteria; differential diagnosis; treatment and prognosis